THE EFFECT OF HUMAN CAPITAL INVESTMENT AND WORKFORCE IN THE FISHERIES SECTOR ON THE WELFARE OF THE COASTAL COMMUNITIES OF TANJUNGBALAI CITY, NORTH SUMATRA - Ibnu Rizal Mubarok; Sri Ramadhani; Muhammad Ikhsan Harahap (International Journal of Economics, Business and Accounting Research (IJEBAR), 2023)
This research aims to assess the impact of investment in human resources and labor in the fisheries sector on the welfare of residents in Tanjungbalai City, North Sumatra. This research approach uses quantitative methods by collecting data through questionnaires to respondents. The results of the research show that investment in human resources has positive impact on welfare, which was confirmed by the t-test results with a significance value of 0.009 < 0.05. This indicates a significant influence, with an influence of 0.05 based on the coefficient. However, Labor does not have a significant impact on community welfare, as stated It can be seen from the t calculated probability value of 0.016 which is greater than 0.05 at the 5% significance level. Therefore,it can be concluded that labor does not have a significant effect on the welfare of coastal residents. Keywords: Human Capital Investment, Fisheries, Community Welfar